Integrated Event Tourism Packaging in National Strategic Areas: A Collaborative Planning Model for SAMOTA, Indonesia - Sirajuddin; Ramdah Radjab; Ida Ayu Yadnya Pidada Sari Dewi Utami Pidada; Endang Sri Wahyuni; Rochmah Dewi Suryani (Journal of Tourism Sustainability, 2025)
Purpose: This study aims to formulate and validate an integrated event tourism package planning model for the SAMOTA National Strategic Tourism Area (KSPN) in Sumbawa, Indonesia. It addresses the critical gap in existing destination management, where flagship events and natural attractions are often marketed in silos, limiting their economic impact and sustainability. Design/methodology/approach: The study adopts a Research and Development (R&D) approach utilizing the 4-D Model (Define, Design, Develop, Disseminate). Data were collected through in-depth interviews with penta-helix stakeholders, including government officials, local communities, and cross-regional travel agencies (Lombok, Bali, and Makassar). The resulting model underwent expert validation to ensure feasibility and market relevance. Findings: The research produced a "Collaborative Event Tourism Planning Model" that effectively integrates the SAMOTA International Festival (SIF) with iconic destinations (Moyo Island, Saleh Bay, and Tambora). The findings demonstrate that cross-regional stakeholder collaboration—specifically involving travel agents in the co-creation process—is the primary driver for building market confidence and expanding distribution channels. The model yielded segmented tourism packages (2D1N, 3D2N, and Full Day) that successfully extended tourists' length of stay. Originality/value: This study contributes to the event tourism literature by providing a validated, visual planning framework that links event scheduling with destination product packaging. It offers a practical roadmap for Destination Management Organizations (DMOs) to transform sporadic events into sustainable tourism products through structured multi-stakeholder synergy.